2001
DOI: 10.4315/0362-028x-64.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Bacteria to Beef from Steam-Pasteurized Carcasses

Abstract: The extent to which a bacterial cocktail containing equal numbers of Pseudomonas fragi NCTC 10689, Listeria monocytogenes BL5/2, Salmonella Typhimurium LT2, and Escherichia coli JM 109 attached to loin surface cuts (7 by 5 cm) derived from steam-pasteurized beef carcasses has been evaluated. The extent of attachment was categorized as loosely attached (removed by rinsing), firmly attached (released by stomaching), and irreversibly bound. No significant difference (P > 0.10) in the attachment of bacteria to ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It was shown that retention of the pathogen after water rinses was significantly higher on lean tissue than on adipose tissue. In other work (59), it was demonstrated that irreversible attachment of E. coli to loin cuts was independent of whether the carcass had undergone a steam pasterization treatment. Use of bioluminescent E. coli showed that cells bound preferentially to cut edges and convoluted areas on the loin surface, and could not be removed by rinsing.…”
Section: And Inmentioning
confidence: 97%
“…It was shown that retention of the pathogen after water rinses was significantly higher on lean tissue than on adipose tissue. In other work (59), it was demonstrated that irreversible attachment of E. coli to loin cuts was independent of whether the carcass had undergone a steam pasterization treatment. Use of bioluminescent E. coli showed that cells bound preferentially to cut edges and convoluted areas on the loin surface, and could not be removed by rinsing.…”
Section: And Inmentioning
confidence: 97%
“…However, there may also be methodology difficulties with recovery of bacteria from chilled carcases as the bacteria may be sublethally injured by the combination of chilling and reduced water activity rendering them non-cultivable. During chilling, some bacteria may become firmly attached to the meat or embedded into the meat tissue and thus not be readily recoverable by swabbing (Warriner et al, 2001). The microbial levels found at this point in the process reflect the VTEC contamination level entering the food chain from the slaughterhouse.…”
Section: Proposed Harmonised Epidemiological Indicators (Heis)mentioning
confidence: 99%
“…This was performed in a laminar flow cabinet and yielded approximately 6 log 10 cfu cm À2 . The meat pieces were then left at room temperature for 30 min to allow for bacterial attachment (Warriner et al, 2001). Following attachment, each excised sample in the treatment tray was sprayed with the dairy extract (LactiSAL Ò ) as follows.…”
Section: Inoculation Of Meat Surfacesmentioning
confidence: 99%